To act or not to act? Student-athlete perceptions of social justice activism - Intosh, Andrew Mac; Martin, Eric M.; Kluch, Yannick (Psychology of sport and exercise, 2020)
Issues related to social justice and activism have always permeated sports, but recently, due to the high profile cases of several elite-level athletes (i.e., Colin Kaepernick, Megan Rapinoe), these issues have become much more prominent in the contemporary sporting climate. Even though these highly visible actions are publicized in today’s media environment, little is known about how collegiate student-athletes perceive engaging in social justice activism. Therefore, the current study surveyed 2,092 collegiate student-athletes on their attitudes toward activism engagement using a theory of planned behavior framework with particular attention paid to how gender and ethnicity/race influenced these relationships. A series of MANOVAs indicated that female student-athletes, in relation to male student athletes, and student-athletes of color, in comparison to White student-athletes, held higher perceptions on most of the subscales related to activism. A hierarchical multiple regression analysis indicated attitudes, perceived behavioral control, and subjective norms were significant predictors of athletes’ intention to engage in activism. In addition, interactions of the three predictors with race and gender influenced the final regression model indicating the strength of each predictor was impacted by athlete race and gender. Future research directions and implications for programming in relation to study findings are discussed. •College student-athletes scored high on all four predictors of activism.•Athletes who held less privileged identities in American society were more likely to indicate they would engage in activism.•Perceived behavioral control, attitudes toward activism, and subjective norms predicted athletes’ intentions to engage in activism.•The final regression model indicated the strength of each predictor was impacted by athlete race and gender.